Menumbuhkembangkan Potensi Promosi Desa Wisata dengan Sentuhan Seni di Desa Watukarung, Pringkuku, Pacitan, Jawa Timur - Cito Yasuki Rahmad (Abdi Seni, 2022)
Cultural diversity and natural beauty make the southern part of Java, particularly the coastal villages, well-known for tourist objects, both cultural and natural. Watukarung Village is one of the most fascinating tourist destinations in Pacitan Regency. Watukarung Village, in addition to natural beach attractions, offers beautiful views. Watukarung Village contains tourism assets with the potential to be developed. The potentials of Watukarung Village may immediately stimulate tourist growth, which will have an impact on the community around tourism. On the other hand, the positive potential of Watukarung Village people in the face of limitations must be fostered. These issues must be resolved by enhancing the existing potential through the use of art in the promotion of tourism villages through trainings. This activity is very beneficial to the people of Watukarung Village because it allows village residents to upgrade their skills in developing community resources and natural resources in the village, allowing the community to actively participate in developing their village’s potential through creative fields with a touch of art.